A bioassessment of the fish populations in the Ohio River near Zimmer power plant - Smith, Amanda (My University, 2015)
The primary objective of this annual study was to determine the potential impacts of the Zimmer coal-burning power plant on the Ohio River ecosystem. Physiochemical and biological data were collected from upstream control sites and downstream experimental sites. Fish, as bioindicators, were collected by the use of electrofishing, hoop nets, and gill nets. The modified Ohio River Fish Index (mORFIN) was calculated. Data collected downstream and upstream were comparable in terms of abundance, biomass, and the mORFIN. The physiochemical data were within acceptable water quality standards. The physiochemical data were similar across all sites and followed the typical seasonal pattern for the River. Overall, the results suggest that the Zimmer power plant has had no significant impact on these areas of the Ohio River.
Color poster with text, illustrations, maps, tables, and graph.
Keywords: bioassessment; Fishes--Ohio River; Ohio River--Environmental conditions; Power-plants--Environmental aspects; Posters